2017
DOI: 10.1155/2017/6106959
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Fridericia formosa (Bureau) L. G. Lohmann (Bignoniaceae) Extracts and Constituents

Abstract: A phytochemical study of Fridericia formosa (Bignoniaceae) ethanol extracts of leaves, stems, and fruits was guided by in vitro assays against vaccinia virus Western Reserve (VACV-WR), human herpes virus 1 (HSV-1), murine encephalomyocarditis virus (EMCV), and dengue virus type 2 (DENV-2) by the MTT method. All the ethanol extracts were active against DENV-2, HSV-1, and VACV-WR with best results for the fruits extract against DENV-2 (SI > 38.2). For VACV-WR and HSV-1, EC50 values > 200 μg mL−1 were determined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The phytochemical characterization by TLC and UPLC-EM and the antiviral activity of Cissus erosa observed in this study are in agreement with the literature data, since poliphenols, like flavonoids are one of the major class of secondary metabolites with antiviral activity against several viruses (Kamboj et al 2012;Johari et al 2012;Brandão et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The phytochemical characterization by TLC and UPLC-EM and the antiviral activity of Cissus erosa observed in this study are in agreement with the literature data, since poliphenols, like flavonoids are one of the major class of secondary metabolites with antiviral activity against several viruses (Kamboj et al 2012;Johari et al 2012;Brandão et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…For the other plants indicated for the purpose of mitigating malnutrition, the studies found do not correlate directly with these properties, but show that they are special with high therapeutic potential. Thus, Brandão et al (2017) demonstrate that extracts of leaves, stems and fruits of Fridericia formosa have antiviral activity, being considered of interest for the development of new antiviral drugs. Regarding Ticorea tubiflora, there are no data on its pharmacological properties, however, Campelo et al (2013) demonstrated species from the Rutaceae family, such as Citrus limon, were able to reduce urea, triglyceride and uric acid levels and improve renal function, probably due to the presence of monoterpenes.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cell LLC-MK2 (ATCC ® CCL-7™) and normal human lung fibroblast cell MRC-5 (ATCC ® CCL-117™) were cultured in Dulbecco's modified Eagle's medium (DMEM, Cultilab, Campinas, SP, Brazil) at 37 °C, in 5% CO 2 atmosphere, supplemented with 5% fetal bovine serum, 50 μg/mL gentamicin, 100 U/mL penicillin and 5 μg/mL amphotericin B (Brandão et al, 2017).…”
Section: Cell Culture and Virusmentioning
confidence: 99%
“…LLC-MK2 and MRC-5 cells were exposed to different concentrations (800 to 0.125 µg/mL) of extracts/ fractions/compounds for 72 h (Brandão et al, 2017). After incubation, cell viability was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, Merck) assay at a concentration of 2 mg/ mL in phosphate buffered saline (PBS) (Brandão et al, 2017;Twentyman, Luscombe, 1987).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation